Identification of Cardiomyopathy-Associated Circulating miRNA Biomarkers in Muscular Dystrophy Female Carriers Using a Complementary Cardiac Imaging and Plasma Profiling Approach - Florian, Anca; Patrascu, Alexandru; Tremmel, Roman; Rösch, Sabine; Sechtem, Udo; Schwab, Matthias; Schaeffeler, Elke; Yilmaz, Ali (Frontiers in Physiology, 2018)
Background - Different from males with Duchenne/Becker muscular dystrophy (DMD/BMD) in whom overt myopathy is the rule, muscular dystrophy (MD) female carriers are mostly free of skeletal muscle symptoms. However, similar to MD males, these females are also prone to cardiomyopathy. Methods - Twenty-nine female MD carriers and 24 age-matched healthy female controls were prospectively enrolled. All MD carriers and controls underwent comprehensive cardiovascular magnetic resonance (CMR) studies as well as venous blood sampling on the same day. Results - An impaired left ventricular (LV) systolic function was detected in 4 (14%) MD carriers only while late gadolinium enhancement (LGE) indicative of myocardial fibrosis was present in 13 (45%) - with an exclusively non-ischemic pattern. Six miRNAs were significantly up-regulated in MD carriers compared to female controls: miR-206 (103-fold increase, p <0.0001), miR-222 (41-fold, p <0.0001), miR-26a (4-fold, p = 0.029), miR-342 (27-fold, p <0.0001), miR-378a-3p (minimum 3600-fold; almost undetectable in controls, p = 0.013), miR-378a-5p (64-fold, p <0.0001); only two miRNAs were substantially down-regulated in MD carriers: miR-144 (p <0.0001) and miR-29a (p = 0.002) (both undetectable in carriers). A significant down-regulation of the miR-29c (<0.001-fold, p=0.006) was observed in MD carriers with abnormal CMR findings (comprising functional and/or structural abnormalities) compared to those with normal CMR examinations. Univariable analyses regarding the presence of abnormal CMR findings resulted in four significant variables: LV-EDVi, LV-ESVi, an elevated plasma creatine kinase (CK), and decreased serum miR-29c levels. In subsequent multivariable analysis, the only independent predictor for an abnormal CMR among MD carriers was circulating miR-29c (OR 0.99, 95 % CI 0.98-0.99, p =0.037). Moreover, an elevated CK and/or a downregulated miR-29c level (<0.05*10-3) resulted in an improved AUC value of 0.79 (0.62 – 0.97, p=0.007) (79%, 80% and 80%, sensitivity, specificity and overall accuracy) for the CMR-based diagnosis of cardiomyopathy in MD carriers when compared to using the two parameters individually,. Conclusion - In female MD carriers, down-regulation of circulating miR-29c relates to the presence of functional and/or structural cardiac abnormalities (as detected by CMR) and appears to be a promising novel biomarker for an early diagnosis of cardiomyopathy.